Occurrences of Deep-Seated Creeping Landslides in Accordance with Hydrological Water Storage in Catchments - Kuo, Chih-Yu; Lin, Shen-En; Chen, Rou-Fei; Hsu, Ya-Ju; Chang, Kuo-Jen; Lee, Shin-Ping; Wu, Rou-Ying; Lin, Ching-Weei; Chan, Ya-Hsin (Frontiers in Earth Science, 2021)
Rainfall is one of the most important triggers of both shallow debris flows and deep-seated landslides. The triggering mechanism involves the process of water infiltration into the failure zone. For deep-seated landslides, the deeper and more extensive failure surfaces delay the effect of the process and thus delay landslide initiations. The delay is difficult to assess, especially if the sites only have scarce or insufficient monitoring data. Under these circumstances, we illustrate that the occurrences of landslides can be estimated by their correlations with the phenomenological water storage index (WSI) of a given catchment. In the present study, a total of five deep-seated landslides in TienChih (4) and SiangYang (1) are investigated. The displacements of the landslides were recorded by global positioning system (GPS) and the WSI was modelled using the tank model. The result demonstrates that the WSI correlates closer in time to the landslide motion than the rainfall, and the WSI thresholds for the landslides are inferred. Thus, this technique can be applied as an associated method to evaluate landslide initiation.